EFEKTIFITAS PENDEKATAN TUTOR SEBAYA DALAM MENINGKATKAN KETERAMPILAN MENGOPERASIKAN SOFTWARE CORELDRAW BAGI SISWA TUNARUNGU KELAS XI DI SLB YPAC SUMBAR - Syafrina Yanti (Universitas Negeri Padang, 2015)
Abstract: This research is motivated by the problems that investigators found in special schools YPAC West Sumatra. This school is no IT learning about graphic design, in particular the development of Software Coreldraw. Viewed in terms of the benefit is great to support the skills of children with hearing impairment in the design world garfis. But the teacher just taught merely to note, even though the potential of the child's good enough to be developed, considering the child with special needs.In this study, researchers used the experimental method in the form of pre-experimental design or often also referred to as quasi experiment with the type of one group pretest-posttest design. In this study tests performed twice: before the experiment and after the experiment. Tests were performed prior to the experiment (01) is called pretest, and tests after the experiment (02) called the posttest. The value of the pretest and posttest processed and compared using the Mann Whitney test.From the results of the study revealed that children's ability to operate Software Coreldraw when analyzed using the Mann Whitney test. Retrieved Uhit = 0.5 and Utab = 0 to n = 4 at significant level of 95% and α = 0.05. The alternate hypothesis is accepted because Uhit> Utab, so it is evident that peer tutors approach is effective in improving the skills operate software CorelDraw for deaf children in SLB YPAC West Sumatra. Key words :Coreldraw Software Operation; Peer Tutoring Approach; With Hearing Impairment Children